Apprenticeship education and school-based vocational programmes in the Swedish upper secondary school : different tracks towards the same goal? - Paul, Enni [Verfasser]; Gafvels, Camilla [Verfasser] (My University, 2021)
"Apprenticeship education is formally a part of the Swedish upper secondary school Vocational Education and Training (VET). Half of the educational time is work based, as compared to a minimum of approximately 14 percent in the school-based VET programs. However, apprenticeship education is based on the curriculum of the school-based VET programs, which seems contradictory according to a situated perspective on learning. The purpose of this small-scale ethnographic case study, is, thus, to explore difFerences in the vocational knowing afforded in the Swedish apprenticeship education compared to school-based education and how this shapes participation in the workplace. The results highlight how different dimensions of knowing intersect with ways of being, which sets the participation of apprenticeship students and VET-school students’ in the workplace a part. This study argues that the current way of organizing the apprenticeship education seems to rest upon a failure to recognize differences in ways of knowing, such as knowing that and knowIng how, or that the situated character of learning in two different practices, school and workplaces, will lead to development of different aspects of vocational knowing. This failure to recognize these differences has consequences for apprenticeship students, as their knowing is assessed on the basis of aims in the curriculum originally formulated for the school-based VET." (Author's abstract ; BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; S 1.3.3 Vollzeitschulische Berufsausbildung; S. 1.3 Berufliche Erstausbildung; 370; Schweden; Berufsbildung; Schulische Berufsausbildung; Fachwissen; Handlungskompetenz; Lernort; Curriculum; Fallstudie